Facing Economic Recession in Nigeria: Lessons from Umar Ibn Al-Khattab’s Economic Policies - Khalid Ishola Bello (Asy-Syari'ah, 2024)
Abstract: Economic conditions are dynamic and can shift from prosperity to adversity, affecting individuals and nations. This paper examines the socioeconomic recession during the early Islamic era under the leadership of Umar ibn Al-Khattab, exploring its causes, remedies, and eventual recovery. Umar’s governance marked by compassionate leadership, adaptive policies, and resource prioritization provides valuable lessons for addressing contemporary economic challenges. Nigeria, which is facing economic recessions characterized by unemployment, inflation, and resource mismanagement, can use these lessons to mitigate its economic woes. This study employs a historical and content analysis of early Islamic economic policies, a comparative analysis of Nigeria’s current challenges, and policy reviews. This highlights the need for empathetic leadership, legislative flexibility, effective resource allocation, and integration of Islamic social finance mechanisms, such as zakāt and waqf, into Nigeria’s socioeconomic framework. Nigeria can enhance its economic resilience and inclusivity by fostering transparency, social justice, and collaboration while addressing systemic inequities.